Uji Pengaruh Surfaktan Tween 80 Dan Span 80 Terhadap Solubilisasi Dekstrometorfan Hidrobromida - Rina Wahyuni; Auzal Halim; Rina Trifarmila (STIFARM Padang, 2014)
The solubilization of dextromethorphan hydrobromide using Tween 80 and Span 80 has been studied. CMC’s value of Tween 80 and Span 80 are determined by surface tension method using Du Nouy Tensiometer and refractive index method using ABBE refractometer. The solubility of dextromethorphan hydrobromide using Tween 80 and Span 80 was evaluated at concentrations below the CMC point, above the CMC point and at CMC point. CMC’s value of Tween 80 and Span 80 respectively are 5,9 µg/mL and 6,3µg/mL. The solubility of dextromethorphan hydrobromide using Tween 80 was greater than Span 80 at concentration above the CMC’s value.